Wheat Culture and Productivity Trends in Wheat Production in the United States, 1867-1914: A Comment - Page, Walter P. (The Review of Economics and Statistics, 1974)
3. While he discusses it in general terms, Mr. Flick fails to present the proposed reformulation of my approach in concise mathematical terms. Hence I find it impossible to determine to what extent it involves simply introduction of a different terminology rather than a substantively different argument. He introduces the new concept of Pollution Services. If this is done with the intention to present new factual information, effect on the material conclusion reached at the end of the argument to be nil. But even if the additional information thus conveyed is intended to be utilized not in this, but in some other context, I would be inclined to question the appropriateness and the intuitive appeal of this particular concept: while air may be viewed industries of by-products, to what substance would Mr. Flick ascribe the function of relieving the airports of the unwanted byproduct consisting of noise generated by landing and departing aircraft? The quantitative approach to the analysis of environmental repercussion within the framework of generalized input-output analysis outlined by me can and certainly will be superseded by more effective formulations; Mr. Flick's critical remarks and positive proposals do not seem however to point in the right direction. presented in my paper entitled Material Income, Economic Structure, and Environmental Externalities, in Measurement of Economic and Social Performance, edited by Milton Moss, National Bureau of Economic Research Press, New York (forthcoming 1974).